Labrador Sea bottom water provenance and REE exchange during the past 35,000 years - Blaser, Patrick; Gutjahr, Marcus; Pöppelmeier, Frerk; Frank, Martin; Kaboth-Bahr, Stefanie; Lippold, Jörg (Earth and planetary science letters, 2020)
Deep waters of the Labrador Sea (LS) are important contributors to the Atlantic Meridional Overturning Circulation, but their water mass structure has been highly variable and sensitive to climatic changes on different time scales. The LS is also an area of intense exchange of rare earth elements (REE) between seawater and the underlying sediments, which complicates the reconstruction of past deep water provenance based on radiogenic neodymium (Nd) isotopes. Most notably, Northwest Atlantic Bottom Water exchanges Nd with Archaean age Laurentian detritus, resulting in a significant shift to less radiogenic Nd isotope signatures before it enters the North Atlantic to form the deep part of North Atlantic Deep Water. Here we show that the authigenic fractions of LS core top sediments carry Nd isotope signatures intermediate between bottom water and detritus and thus reflect pore waters that incorporate a mixture of both signatures. We furthermore find that detrital imprints on pore waters led to shifts of REE patterns in the authigenic fraction towards detrital signatures in the past during times of enhanced supply of glacially eroded material from Hudson Bay to the LS, as recorded by radiogenic lead isotopes. This allows an estimation of the intensity of past benthic REE exchange inside the LS. We exploit variations in the mid REE enrichment in the authigenic phase to propose a correction to one LS Nd isotope record for detrital imprints originating from pore water exchange. The corrected ϵNd signatures are argued to more accurately reflect those of past bottom waters. This correction results in past LS bottom water signatures of −16 ± 1 during MIS 2 and 3, considerably less radiogenic than today. This implies that no southern sourced waters advanced into the LS during the last 35 ka and instead supports continuous bottom water sourcing from the Nordic Seas. It thus seems likely that LS bottom waters supplied unradiogenic Nd to abyssal Glacial North Atlantic Bottom Water in the Northwest Atlantic, as was previously hypothesized.